Frequency regulation of hybrid power system using firefly algorithm. (3rd June 2022) - Gorripotu, Tulasichandra Sekhar; Pilla, Ramana
In the present work, firefly algorithm (FA)-based cascaded PD-PID with filter controller (PD-PIDF) is implemented for the hybrid power system to keep the frequency within the limits. At first, a two-area hybrid power system is proposed, considering thermal and distributed power units in area 1, and hydrothermal units in area 2. The cascaded PD-PIDF controller parameter values are optimised using the integral time multiplied absolute error (ITAE) criterion. The proposed system is analysed under three cases by applying step load perturbations (SLPs) and noise signals at possible areas. The superiority of cascade PD-PIDF controller is shown by comparing with recently published results. Finally, sensitivity analysis is performed to demonstrate the cascaded PD-PIDF controller capability while varying system parameters and conditions.